Hydrogeological Analysis of Cretaceous and Tertiary Aquifers in Semiarid Sokoto Basin, Northwestern Nigeria: Implications for Sustainable Groundwater Development - Wali, Saadu U.; Alias, Noraliani; Harun, Sobri Bin; Mohammed, Ibrahim U.; Garba, Muhammed L.; Atiku, Mudassir; Gada, Murtala A.; Hamisu, Isah (Global Journal of Earth Science and Engineering, 2023)
Groundwater development in arid and semiarid regions is accelerated by expanded irrigation farming, industrialisation, and municipal water supply. This study provides a detailed hydrogeological analysis of sedimentary aquifers of the Sokoto basin, Northwestern Nigeria, for improved water resource development and management. Hydrogeological data, including static water level (Swl), pumping water level (Pwl), pumping test (Pt), and estimated yield (Ey), were analysed. A total of three hundred (300) observations on Swl, Pt, Pwl, Ey, and Hps were derived from boreholes and analysed using Factor analysis (FA) and Regression analysis (RA). Results showed that Gwandu Formation is the most prolific aquifer. Boreholes can yield more than 24000 litres per hour (L/h). This was followed by The Kalambaina limestone aquifer, which has the potential to yield about 15000 (L/h). However, the Taloka Formation is characterised by very poor aquifers in most of the basin, though along the Jega-Dogon Daji axis, boreholes can yield more than 24000 (L/h). Likewise, boreholes tapping the Wurno Formation can produce a maximum yield of 24000 (L/h). Estimated yields from boreholes were less than 1500 (L/h) from the Gundumi aquifer, and the maximum borehole yields were 17760 (L/h) in the Illo aquifer. Statistical modelling showed that all the analysed variables are significant concerning groundwater potentials and variability of borehole yields in the study area. Therefore, future groundwater resource development in the study area should be based on a proper analysis of the geological configurations of the Sokoto basin. This study provides an outlook on the groundwater potentials of the study area and aquifers that can provide a basis for sustainable groundwater development policy. Thus, the study has shown how multivariate and regression analysis can be used to study the hydrogeological conditions of a particular basin. Therefore, it is hoped that this study’s findings will inspire other researchers to take a comparable approach.